Threatened Identity: Self Psychology Informed Communication for Serious Illness Care - Daniel Shalev; Indrany Datta-Barua; Leah B. Rosenberg; Keri O. Brenner; Theodore Scheel; Danielle Chammas (Journal of Palliative Medicine, 2026)
Serious illness threatens both the body and the self: the coherent, continuous sense of who one is, from bodily integrity to psychosocial identity. When illness disrupts identity and patients confront mortality and dependence, a range of responses may follow, including behaviors such as relentless demands, devaluation of clinicians, insistence on additional treatment, or rage at perceived care failures. These presentations are often labeled “narcissistic,” yet such a formulation can foreclose clinical understanding. Heinz Kohut’s self psychology offers a more generative framework: one that understands these behaviors as attempts to preserve self-cohesion when illness threatens identity, autonomy, competence, and roles. Because needs for recognition, connection, and reliable support persist throughout life, serious illness often exposes vulnerabilities that were previously stabilized through work, relationships, and social roles. Informed by self psychology’s core concepts—self-object needs, mirroring, idealizing, twinship, and empathic attunement—this paper presents practical serious illness communication tools designed to reduce interpersonal conflict, strengthen therapeutic alliance, and support patients in maintaining a coherent sense of self as illness progressively reshapes what is possible.